HUBUNGAN DUKUNGAN SOSIAL DAN TINGKAT SPIRITUAL DENGAN KUALITAS HIDUP LANSIA DI RW 04 TELAGA MURNI BEKASI - Nabilah Tiani Rachman (2021)
Old age is the final stage in human life. In this phase the elderly will experience physical, mental, social and spiritual health problems that will affect the quality of life of the elderly. This study aims to determine the relationship between social support and spiritual level with the quality of life of the elderly. This research uses quantitative research with cross sectional approach. The sample of this study amounted to 89 respondents who were taken using simple random sampling. Measurement of social support using the Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire, measuring spiritual level using the Daily Spiritual Experience Scale (DSES) and measuring quality of life using the WHOQOL-BREF questionnaire. The results of the univariate test showed that 48.3% had high social support, 51.7% had a high spiritual level and 67.4% had a good quality of life. The results of the Chi-Square test obtained p-values respectively (p = 0.006 and p = 0.042). The conclusion of the study is that there is a relationship between social support and spiritual level with the quality of life of the elderly. Therefore, it is necessary to increase the participation of the elderly in group activities and spiritual activities so that the quality of life becomes better.